REGIONAL HEAD (PRODUCT OF A DEMOCRATIC SYSTEM) AS A ROLE MODEL AND ANTI-FRAUD REPRESENTATION - Cakra Arbas (Association of Certified Fraud Examiners Indonesia Chapter, 2019)
The Constitution mandates that